Nonlinear state-space predictive control with on-line linearisation and state estimation - Ławryńczuk, Maciej (Zielona Góra: Uniwersytet Zielonogórski)
This paper describes computationally efficient model predictive control (MPC) algorithms for nonlinear dynamic systems represented by discrete-time state-space models. Two approaches are detailed: in the first one the model is successively linearised on-line and used for prediction, while in the second one a linear approximation of the future process trajectory is directly found on-line.
Keywords: process control; model predictive control; nonlinear state-space models; extended Kalman filter; on-line linearization